Effectiveness of Health Promotion Program in People with Uncontrolled Type 2 Diabetes at a Tertiary Care Hospital, Samut Sakorn Province - Pimpava, Anongrak; Choonthong, Rattana; Sirirat, Nongnuch (Journal of Thailand Nursing and Midwifery Council, 2024)
Introduction Type 2 diabetes is a non-communicable disease characterized by an increasing incidence with advancing age, leading to complications and premature mortality. Health promotion for people with uncontrolled diabetic is an approach to continuously control their blood sugar. Objective To examine the effects of a health promotion program on health promoting behaviors and hemoglobin A1C in people with diabetes. Design This study employed a quasi-experimental design with two-group pretest and posttest, applying Pender’s health promotion model as the conceptual framework. Methodology Participants consisted of 60 people diagnosed with Type 2 diabetes, with hemoglobin A1C of over 7% in the past three months. They received treatment at a tertiary care hospital in Samut Sakhon province between October and December 2020. The participants were purposively selected based on following inclusion criteria: 1) residing in Ban Phaeo sub-district, Samut Sakhon province, 2) no cognitive decline and able to read and write Thai well, 3) having a contactable phone number and being able to use a smartphone, and 4) willing to participate in the study. The sample size was determined based on Krejcie and Morgan’s principle, with 30 participants each in the experimental and control groups, assigned purposively. The research tools included a 12-week health promotion program delivered in group sessions, with a content validity index of .85. Data collection tools consisted of a demographic questionnaire, a record form, and a health promoting behavior questionnaire, which had been validated in a group similar to the sample, obtaining a Cronbach’s alpha coefficient of .85. Data were collected from October to December 2020. The control group received routine care, while the experimental group participated in the 12-week group health promotion program in addition to routine care. Data were analyzed using descriptive statistics, including frequency, percentage, mean, standard deviation, and median. Inferential statistics included Chi-square tests, Paired t-tests, Independent t-tests, Mann-Whitney U tests, and Wilcoxon signed-rank tests. Results The control and experimental groups did not significantly differ in personal characteristics, except for the time since diabetes diagnosis, with the control group having a median of 3 years and the experimental group having a median of 5 years. After participating in the program, the experimental group showed significant higher in overall health-promoting behaviors, including nutrition, exercise, stress management, and medication taking, compared to before the program (Z = -4.705, -4.794, -4.556, -3.625, -4.580, p < .001). However, these were not significantly different from the control group (Z = -0.573, -0.834, -0.243, -1.939, p > .05), except for medication taking, where the experimental group scored significantly higher than the control group (Median = 4.00, Z = -2.441, p = .015). Additionally, the experimental group had a significantly lower hemoglobin A1C after the program (Z = -3.259, p = .001) but did not differ significantly from the control group (Median = 7.25, Z = -1.761, p > .05). Recommendation The healthcare team at a tertiary care hospital, whose context closely aligns with this study, can apply the health promotion program with routine care to monitor and support behavioral modifications in people with uncontrolled Type 2 diabetes.